2021
DOI: 10.1002/micr.30734
|View full text |Cite
|
Sign up to set email alerts
|

Application of intraoperative indocyanine green angiography for detecting flap congestion in the use of free deep inferior epigastric perforator flaps for breast reconstruction

Abstract: Background: The use of intraoperative indocyanine green (ICG) angiography has been well documented for confirmation of arterial perfusion in transferred free flaps. However, no previous report has yet focused on whether ICG angiography can be used to detect congestion in free flaps. The present report investigates the feasibility of ICG angiography for detecting flap congestion intraoperatively through illustrative cases. Methods: From September 2019 to September 2020, 65 consecutive female patients who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 19 publications
0
30
1
Order By: Relevance
“…The skin flap was elevated above this fascia, and the deeper fat was saved ( Figure 1 ). After the elevation was completed, the flap perfusion was confirmed on indocyanine green angiography [ 18 ]. Recipient vessels were prepared within or in the adjacent of the defect after tumor excision.…”
Section: Methodsmentioning
confidence: 99%
“…The skin flap was elevated above this fascia, and the deeper fat was saved ( Figure 1 ). After the elevation was completed, the flap perfusion was confirmed on indocyanine green angiography [ 18 ]. Recipient vessels were prepared within or in the adjacent of the defect after tumor excision.…”
Section: Methodsmentioning
confidence: 99%
“…In this way we are able to identify the areas where the blood supply was lower and we usually resected them, thus reducing the risk of distal flap necrosis. Furthermore, a recent study showed also how the application of intraoperative ICG angiography can be safely used to predict venous congestion after free tissue transfer (Yoshimatsu et al, 2021).…”
Section: Surgical Techniquementioning
confidence: 99%
“…Its primary use has since switched to that of lymph node mapping, angiography and fluorescence-guided surgery. Intravenous administration allows quantitative assessment of tissue perfusion intraoperatively, allowing assessment of skin flap viability and congestion, prompting immediate revision, as opposed to future operations after flap failure [15][16][17] ; ICG angiography has also been demonstrated as a bedside tool to improve detection of reduced perfusion postoperatively 18 . Besides angiography for flap perfusion, ICG has also been described during intra-cranial aneurysm surgery 19 , coronary artery bypass graft surgery 20 , and is currently under investigation to evaluate whether it can reduce the anastomotic leak rate in colorectal cancer resection 21 .…”
Section: Introductionmentioning
confidence: 99%